Soil Conservation as Related to Engineering Projects - Pani, M.C. (Journal of Soil and Water Conservation, 2022)
The magnificant creation of nature is this earth on which we live. In the initial stage the world must have been consisting of steep mountains and deep ocean. The surface of the steep slopes of the mountain have been exposed to all kinds of weather and climatic conditions for ages and have been disintergratng. From time to time mass movements of materials have taken place either by sliding or otherwise from higher elevation to the lower elevation. Large tracts of land of gentle gradient has been formed on the surface of the earth by action of water working for thousand of years. The Sun which is the main source of energy has lifted enormous volume of water year after year and spread over the surface of the earth to wash down the weathered material called soil to lower elevation to form flat and alluvial plains. Many of the steep mountains have changed to flat land due to continuous movement of soil from their surfaces. Thus we find the beautiful land of gentle gradient and fertile alluvial delta on the surface of the earth which are most suitable for human habitation.